Evidência genética da presença de Farfantepenaeus paulensis (Pérez-Farfante, 1967) no litoral nordeste do Brasil (Decapoda: Penaeidae) - D'Incao, Fernando (1998)
Northeastern and southern (Ceará and Rio Grande do Sul) Brazilian shrimps were sampled. The species identification was made using morphological and isoeletric focusing methods. Twenty one shrimps of the Farfantepenaeus subtilis species, 19 shrimps of the morphotype II and 14 shrimps of the F. paulensis species were analyzed by isozyme electrophoresis. Eighteen loci and 33 alleles were identified. The alłelic frequencies values and Wright’s fixation index (F) suggest that morphotype II is an equatorial subpopulation of F. paulensis.